Full simplify problem

*To*: mathgroup at smc.vnet.net*Subject*: [mg122261] Full simplify problem*From*: "A. Lapraitis" <ffcitatos at gmail.com>*Date*: Sat, 22 Oct 2011 06:09:48 -0400 (EDT)*Delivered-to*: l-mathgroup@mail-archive0.wolfram.com

Hello, Could anyone explain why the following does not give zero? In[72]:= Assuming[ x == y + z, FullSimplify[ E^x - E^(y + z) ] ] Out[72]= E^x - E^(y + z) Thanks!

**Follow-Ups**:**Re: Full simplify problem***From:*DrMajorBob <btreat1@austin.rr.com>

**Re: Full simplify problem***From:*Andrzej Kozlowski <akoz@mimuw.edu.pl>